Acceptance on open and distance learning method amongst special education needs teachers during movement control order / Nasiha Hanis Yahaya and Zulkifli Abd. Latiff - Yahaya, Nasiha Hanis; Abd. Latiff, Zulkifli (Centre For Media And Information Warfare Studies, 2021)
SEN children needed close guidance and physical assist by teachers, and recent pandemic changes everything. Study focuses in measuring the acceptance of SEN teachers in coping up with the ODL method of teaching during the pandemic. Therefore, study aims to compel how are the Special Education Needs (SEN) teachers’ acceptance on the ODL teaching method during the Movement Control Order (MCO), how does the teaching method and software utilized for ODL during MCO help them in daily teaching and why does ODL teaching method should be sustained based on SEN teachers’ perception? Technology Acceptance Model (TAM) by Davis (1989), highlighted two factors influence the acceptance of human on technology, (1) perceived usefulness and (2) perceived ease of using one. Qualitative research methodology having purposive sampling as the sampling method were chosen. A protocol in-depth interview on four SEN teachers from SMK Tun Haji Abdul Malek, Melaka were conducted. These teachers have experience in teaching visual impairment students and currently teaching Slow Learner students. Findings indicated that SEN teachers’ acceptance on ODL teaching method shows positivity as it helps to build and enhanced their teaching capacity through technological usage. Second finding indicated that interactive and gamification-based learning software helped increased students’ participation in ODL. Thirdly, interestingly, despite the circumstances in integrating oneself with technology and limited participation of students, SEN teachers positively perceived the sustainability of ODL teaching method as it helps to increase long term digital literacy on both SEN teachers and students. This study is significant due to its capability to dive into SEN perspectives and supplement improvision.